2022
DOI: 10.3171/2021.8.jns211321
|View full text |Cite
|
Sign up to set email alerts
|

Neurological event prediction for patients with symptomatic cerebral cavernous malformation: the BLED2 score

Abstract: OBJECTIVE Retrospective patient cohort studies have identified risk factors associated with recurrent focal neurological events in patients with symptomatic cerebral cavernous malformations (CCMs). Using a prospectively maintained database of patients with CCMs, this study identified key risk factors for recurrent neurological events in patients with symptomatic CCM. A simple scoring system and risk stratification calculator was then created to predict future neurological events in patients with symptomatic CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We did not identify infratentorial location as being a significant factor associated with haemorrhage, something that was identified in their manuscript, and other papers [ 20 ]. A recent multi-centre, prospective study examining risk of CCM haemorrhage on multivariable analysis identified large size, eloquent location, and shorter time since last haemorrhage event to be significantly associated with haemorrhage [ 21 ]. Our study identified both large size, eloquent location, and previous symptomatic haemorrhage to be significant, with all of these factors being incorporated into a bleeding risk calculator proposed by the same authors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not identify infratentorial location as being a significant factor associated with haemorrhage, something that was identified in their manuscript, and other papers [ 20 ]. A recent multi-centre, prospective study examining risk of CCM haemorrhage on multivariable analysis identified large size, eloquent location, and shorter time since last haemorrhage event to be significantly associated with haemorrhage [ 21 ]. Our study identified both large size, eloquent location, and previous symptomatic haemorrhage to be significant, with all of these factors being incorporated into a bleeding risk calculator proposed by the same authors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These can be used by clinicians to help categorise haemorrhage risk, and develop patient-focussed management strategies for each CCM, as opposed to each patient. These features have already begun to be utilised in haemorrhage risk calculators [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively low marginal doses are applied compared with malignant tumors, the optimum treatment dose remains uncertain [ 47 ]. Therefore, it is thought that this study, which used a fairly homogeneous dose, considering the number of cases, will contribute to the formation of the literature [ 48 ].…”
Section: Discussionmentioning
confidence: 99%